EFFECT OF KINTEIN AND SALICYLIC ACID ON CARRYFFLOWER (Carthamus tinctorius L.) TOLERENCG WATER-STRESS - & Hamed, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experiment was carried out at the plant garden -Science Dep. of Sciences College of Basic Education, Almustansriyah Univ. the objective was to study the effect of Kinetin and Salicylic  acid at two  growth stages, using split–split plot design  with three replicates .Irrigative treatment (every 3,6,9 weeks) .and main plots , plant regulators (control, Kinetin spray and  Salicylic acid spray ) as sub plots, while,growth regulator spray stages(tillring initiation, flowers budinitiation sub-sub plots     The results were revealed, The Plants which irrigated every 3 and 6 weeks look longer time from 100% flowering to physiological watering(66.67 , 68.22 days)highest number of  heads.plants-1 ( 45 .00 ,38.56  heads.Plant-1.Theplants which  irrigated every  6  weeks  produced highest seed yield( 3159.17 kg .ha-1) harvest index(51.57%) oil percent(37.63).The plants sprayed salicylic acid produc ed highest, plant highest, biological yield ,water use efficiency .The results were revealed possibility  of  Kinetin spraying during the vegetative growth and Salicylic acid during fertilization stage , helpstoincrease seed yield and oil percent.